Oxford studies in political philosophy. Volume 4 - Sobel, David; Vallentyne, Pete; Wall, Steven 1967- (Oxford, United Kingdom Oxford University Press, 2018)
This is the fourth volume of Oxford Studies in Political Philosophy. The series aims to publish some of the best contemporary work in the vibrant field of political philosophy and its closely related subfields, including jurisprudence, normative economics, political theory in political science departments, and just war theory.
Dethroning democratic legitimacy / Zofia Stemplowska and Adam Swift -- The power of public positions: official roles in Kantian legitimacy / Thomas Sinclair -- Institutional legitimacy / Allen Buchanan -- '(Luck and relational) egalitarians of the world, unite!' / Kasper Lippert-Rasmussen -- Varieties of relational egalitarianism / Zoltan Miklosi -- Moralizing liberty / Ralf M. Bader -- May a government mandate more comprehensive health insurance than citizens want for themselves? / Alex Voorhoeve -- Complicity and coercion: toward an ethics of political participation / Alex Zakaras.
Includes bibliographical references and index.
Keywords: Political science -- Philosophy